2020
DOI: 10.1088/1757-899x/769/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proliferative Diabetic Retinopathy in Fundus Images Using Convolution Neural Network

Abstract: Convolution Neural Network (CNN) is one of the techniques under Artificial Neural Network (ANN) used to develop a Deep Learning Neural Network (DLNN) algorithm for detection of Proliferative Diabetic Retinopathy (PDR) on the fundus images. About 116 PDR and 150 Non-Proliferative Diabetic Retinopathy (NPDR) of fundus images retrieved from the publicly available MESSIDOR database applied in this research. This study consisted three objectives that included the execution of two pre-processing techniques on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In 2020, Hassanet al [19] have recommended Fundus Pictures Using Convolution Neural Networks for Proliferative Diabetic Retinopathy Identification. The three goals of this study were to perform two pre-processing methods on the data set, which involved resizing and normalizing the fundus images; establish a deep learning operations and maintenance Artificial Intelligence (AI) network of feature extraction algorithm for identification of PDR on the fundus images; and evaluate the output classification of the network, which took accuracy, sensitivity, and specificity into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2020, Hassanet al [19] have recommended Fundus Pictures Using Convolution Neural Networks for Proliferative Diabetic Retinopathy Identification. The three goals of this study were to perform two pre-processing methods on the data set, which involved resizing and normalizing the fundus images; establish a deep learning operations and maintenance Artificial Intelligence (AI) network of feature extraction algorithm for identification of PDR on the fundus images; and evaluate the output classification of the network, which took accuracy, sensitivity, and specificity into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their experiment demonstrated that both of these networks are capable of detecting NVD with high accuracy and sensitivity. Abu Hassan et al [27] published a paper in which they developed a CNN for detecting PDR in fundus images. Their CNN achieves an accuracy of 73.81%, a sensitivity of 76%, and a specificity of 69%, respectively.…”
Section: Related Workmentioning
confidence: 99%
“…However, according to statistics, by the end of 2017, the total number of health personnel in China was 11.749 million, including 3.39 million practicing (assistant) doctors and 901,000 rural doctors. Although there are a large number of practitioners, compared with the goals in the "Healthy China 2030" plan proposed by China, the number of doctors is far from enough, and some doctors in areas with limited medical resources have a low level of education, although the number of rural doctors is limited [7,8]. Therefore, some patients in areas with limited medical resources cannot obtain efficient treatment plans or long-term follow-up treatment.…”
Section: Introductionmentioning
confidence: 99%